ANALISIS PERENCANAAN DAN PERTANGGUNGJAWABAN APBDes MENURUT PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 DALAM UPAYA MENINGKATKAN PEMBANGUNAN DESA - Orangbio, Vega Virjinia; Tinangon, Jantje J; Gerungai, Natalia (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Village financial management is the whole activity which includes planning, implementation, reporting and accountability of village finances. A sound management of village finances must be managed in accordance with the rules and principles and human resource capabilities that implement them. The purpose of this study is to analyze the suitability of financial management in two inobonto villages with the rules of the minister of home affairs number 113 of 2014 which includes the activities of planning, implementation, and accountability by using qualitative descriptive research method. The results showed the regulation of the minister of home affairs number 113 of 2014 on the management of village finance in the village inobonto two subdistricts bolaang mongondow not fully implemented according to existing rules. For financial planning and execution activities in two village inobonto, not yet transparent information to the public on the budget of village expenditure income. The village financial management system in the village of inobonto 2 has not yet used the village financial system (SISKEUDES). So it is expected that in the village financial management activities in the next budget year should use the village financial system.Keywords: Village financial planning, village financial implementation, village financial accountability, APBDes Permendagri No.113 Year 2014.